Battery Energy Storage Systems in Microgrids: A Review of SoC Balancing and Perspectives - Thales Augusto Fagundes; Guilherme Henrique Favaro Fuzato; Lucas Jonys Ribeiro Silva; Augusto Matheus dos Santos Alonso; Juan C. Vasquez; Josep M. Guerrero; Ricardo Quadros Machado (IEEE Open Journal of the Industrial Electronics Society)
Microgrids (MGs) often integrate various energy sources to enhance system reliability, including intermittent methods, such as solar panels and wind turbines. Consequently, this integration contributes to a more resilient power distribution system. In addition, battery energy storage system (BESS) units are connected to MGs to offer grid-supporting services, such as peak shaving, load compensation, power factor quality, and operation during source failures. In this context, an energy management system (EMS) is necessary to incorporate BESS in MGs. Consequently, state-of-charge (SoC) equalization is a common approach to address EMS requirements and balance the internal load among BESS units in MG operation. In this article, we present a comprehensive review of EMS strategies for balancing SoC among BESS units, including centralized and decentralized control, multiagent systems, and other concepts, such as designing nonlinear strategies, optimal algorithms, and categorizing agents into clusters. Moreover, in this article, we discuss alternatives to improve EMS and strategies regarding the topology of power converters, including redundancy-based topology, modular multilevel converter, cascaded-based converter, and hybrid-type systems. In addition, this article explores optimization processes aimed at reducing operational costs while considering SoC equalization. Finally, second-life BESS units are explored as an emerging topic, focusing on their operation within specific power converters topologies to achieve SoC balance.